Ion channel-mediated mitochondrial volume regulation and its relationship with mitochondrial dynamics - Yujia Zhuang; Wenting Jiang; Zhe Zhao; Wencui Li; Zhiqin Deng; Jianquan Liu (Channels, 2024)
The mitochondrion, one of the important cellular organelles, has the major function of generating adenosine triphosphate and plays an important role in maintaining cellular homeostasis, governing signal transduction, regulating membrane potential, controlling programmed cell death and modulating cell proliferation. The dynamic balance of mitochondrial volume is an important factor required for maintaining the structural integrity of the organelle and exerting corresponding functions. Changes in the mitochondrial volume are closely reflected in a series of biological functions and pathological changes. The mitochondrial volume is controlled by the osmotic balance between the cytoplasm and the mitochondrial matrix. Thus, any disruption in the influx of the main ion, potassium, into the cells can disturb the osmotic balance between the cytoplasm and the matrix, leading to water movement between these compartments and subsequent alterations in mitochondrial volume. Recent studies have shown that mitochondrial volume homeostasis is closely implicated in a variety of diseases. In this review, we provide an overview of the main influencing factors and research progress in the field of mitochondrial volume homeostasis.